2015
DOI: 10.5144/0256-4947.2015.324
|View full text |Cite
|
Sign up to set email alerts
|

Perforated obturator Littré hernia in an elderly woman

Abstract: Obturator hernia is an uncommon condition. It carries the highest mortality amongst abdominal wall hernias, usually presenting in elderly, multiparous and thin ladies. Meckel diverticulum is a rare cause of intestinal obstruction and its existence in an obturator hernia is extremely rare; our literature search revealed only two reported cases. We report the case of a 70-year-old woman who presented with signs and symptoms of intestinal obstruction and peritonitis. An exploratory laparotomy led to diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This phenomenon is more common on the right side[ 6 ] with the proposed theories for lower rates on the left side which is the existence of the sigmoid colon covering the left obturator foramen. [ 7 ] Remarkably, two of three cases of the present case series have been presented as the “left-sided” incarcerated obturator hernias that lead to intestinal obstructions.…”
Section: Discussionmentioning
confidence: 82%
“…This phenomenon is more common on the right side[ 6 ] with the proposed theories for lower rates on the left side which is the existence of the sigmoid colon covering the left obturator foramen. [ 7 ] Remarkably, two of three cases of the present case series have been presented as the “left-sided” incarcerated obturator hernias that lead to intestinal obstructions.…”
Section: Discussionmentioning
confidence: 82%
“…2020; 17(4):e102908. ature (3,4). Thereby, we report this case to discuss significant radiologic findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is uncommon in the adult population (2). The coexistence of obturator hernia and Meckel's diverticulum is extremely rare, with only a few studies reported in the literature (3,4). Although obturator hernias have the highest mortality rate of between 13% and 40% for all abdominal hernias (1), vague signs and symptoms make them difficult to diagnose.…”
Section: Introductionmentioning
confidence: 99%
“…On CT or MRI, a herniating bowel loop with a defect in the inguinal region is observed[ 4 ]. Obturator hernias are typically observed in emaciated and multiparous elderly women[ 9 ]. Therefore, when thin elderly women present with unexplained thigh pain (anterior, medial, or lateral areas), CT or MRI scans for evaluating obturator hernias are recommended.…”
Section: Discussionmentioning
confidence: 99%